Prevalence of articular chondrocalcinosis in elderly subjects in a rural area of Catalonia. Issue 6 (June 1993) - Sanmartí, R; Pañella, D; Brancós, M A; Canela, J; Collado, A; Brugués, J
Abstract : OBJECTIVES–To undertake an epidemiological survey of the prevalence of radiological chondrocalcinosis in the elderly population of Osona, a rural area of Catalonia, north east Spain. METHODS–Knee and wrist radiographs were performed on 261 subjects (141 women, 120 men) aged at least 60 years, who attended a series of 35 general practitioners for various medical problems. RESULTS–Twenty seven subjects had articular chondrocalcinosis, which represents a crude prevalence of 10%. Articular chondrocalcinosis was more often observed in women than in men (14 v 6%). Articular chondrocalcinosis increases in occurrence with age, rising from 7% in subjects aged 60-69 years to 43% in subjects older than 80 years. A similar occurrence of articular chondrocalcinosis was noted in the indigenous population, in which several cases of familial chondrocalcinosis have previously been reported, and in subjects born in other areas of Spain. All but one subject with articular chondrocalcinosis had chondrocalcinosis of the knee. The occurrence of rheumatic disorders did not differ significantly between subjects with articular chondrocalcinosis and those without. CONCLUSIONS–Articular chondrocalcinosis is an age related disorder, which could partly explain the discrepancies in its prevalence reported in previous studies. In most subjects with articular chondrocalcinosis recruited from an unselected population the clinical manifestations are probably mild or even absent.